1985
DOI: 10.3189/1985aog6-1-130-134
|View full text |Cite
|
Sign up to set email alerts
|

Formation Processes of Ice Fabric Pattern in Ice Sheets

Abstract: Experimental studies on the Formation process of the single maximum fabric of ice from its random fabric were carried out using both Greenland Dye-3 ice cores and artificially grown polycrystalline ice. From the observations of the rotation of c-axes of individual grains in thin specimens, an empirical equation was obtained for describing the rotation process of c-axes. Combined with another empirical equation on the relationship between the uniaxial strain of whole specimen and the uniaxial strain in individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
1
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(123 citation statements)
references
References 8 publications
(2 reference statements)
3
118
1
1
Order By: Relevance
“…Rotation of existing grains in polycrystals is described to good approxinIation by the results of AZUnla and Higashi (1985) {2} Azuma and Higashi (1985) deformed thin ice specimens uniaxially and found that the strain in each grain was approximately proportional to the resolved shear stress along its basal plane, with the bulk strain equal to the strain of individual grains averaged over the entire sample. They then found that this model predicts the observed fabric development at Dye 3, Greenland, in the region of normal grain growth, where such a model for an existing population of grains should apply.…”
Section: Results -Fabric Formationmentioning
confidence: 99%
See 3 more Smart Citations
“…Rotation of existing grains in polycrystals is described to good approxinIation by the results of AZUnla and Higashi (1985) {2} Azuma and Higashi (1985) deformed thin ice specimens uniaxially and found that the strain in each grain was approximately proportional to the resolved shear stress along its basal plane, with the bulk strain equal to the strain of individual grains averaged over the entire sample. They then found that this model predicts the observed fabric development at Dye 3, Greenland, in the region of normal grain growth, where such a model for an existing population of grains should apply.…”
Section: Results -Fabric Formationmentioning
confidence: 99%
“…They then found that this model predicts the observed fabric development at Dye 3, Greenland, in the region of normal grain growth, where such a model for an existing population of grains should apply. More recently, Lipenkov and others (1989) have found that the Azuma and Higashi (1985 ) model, modified for uniaxial tension following Fujita and others (1987 ), accurately describes fabric observations in the Vostok, East Antarctica, core.…”
Section: Results -Fabric Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…A single-maximum fabric is usually produced by vertical compression (and divergent horizontal tension) (Azuma and Higashi, 1985) or by simple shear near the base of a glacier (Budd and Jacka, 1989). The authors noted that these different fabrics (single maximum and vertical girdle) are characteristic of different stress conditions, and suggested that their interpretation requires an assumption of discontinuity in the recrystallization and deformation processes that may be attributed to structural softening.…”
Section: Introductionmentioning
confidence: 99%